Co-gasification of biomass and coal in a top-lit updraft fixed bed gasifier: Syngas composition and its interchangeability with natural gas for combustion applications. (15th May 2022) - Quintero-Coronel, D.A.; Lenis-Rodas, Y.A.; Corredor, L.; Perreault, P.; Bula, A.; Gonzalez-Quiroga, A.
Highlights: Biomass-coal co-gasification integrates advantages of feedstock with syngas production. TLUD is a low-cost gasifier with excellent potential for coal-biomass co-gasification. The ignition front propagates faster and is more uniform as biomass share increases. Syngas-NG blends with up to 15 vol% syngas could combust in natural NG burners. Abstract: The co-gasification of biomass and coal is a promising approach for efficiently integrating the unique advantages of different gasification feedstock with syngas production. Additionally, syngas from the co-gasification of locally available biomass and coal could supplement the natural gas used in household and industrial burners. The top-lit updraft gasifier features a moving ignition front that starts at the top and propagates downward through the solids bed, while air enters from the bottom and the gas product flows upwards. This study assesses the co-gasification performance of palm kernel shell and high-volatile bituminous coal in a top-lit updraft fixed bed gasifier using 70, 85, and 100 vol% biomass and equivalence ratios ranging from 0.26 to 0.34. The results indicate that the ignition front propagates faster and is more uniform as the biomass volume increases. Micro GC analysis revealed that the H2 /CO ratio remained in the range of 0.57–0.59, 0.49–0.51, and 0.42–0.46 for experiments with 70, 85, and 100 vol% biomass, respectively. A gas interchangeability analysis showed that syngas-natural gas blends with up to 15 vol% of syngas could combust in atmospheric natural gas burners without modifications. Thus, the top-lit updraft gasifier shows excellent potential for the co-gasification of coal and biomass. Further research on this technology should explore steam as a gasification agent to enhance the syngas energy content and continuous solids feeding.